Twelve tips on how to establish a new undergraduate firm on a critical care unit. (4th March 2017) - Khan, Nasser; Jovestani, Keiarash; Spencer, Craig; Man, Raymond; Pugh, Mark; Woywodt, Alexander
Abstract: Background: Little is known about undergraduate teaching in critical care unit (CrCU) and many undergraduate curricula lack placements in CrCU. Aims: To describe how our CrCU succeeded in developing a novel placement for Year 3 undergraduate medical students. Methods: Particular emphasis was placed on a robust timetable incorporating a variety of activities, a dedicated and thorough induction, and a mix of teaching methods such as formal and informal, consultant-led, and skills. Services allied to CrCU were also utilized. Results: Our new firm has exceeded all expectations and, based on student feedback, received the "Firm of the Year" award for several years in succession. It now serves as a model of undergraduate teaching in our hospital. Conclusions: Educationalists and intensivists should work together to unlock the full potential of this rich learning environment. Professional societies in critical care medicine should take the opportunity to develop more interest in undergraduate medical education.